Instrument of Institutional Empowerment? : An Explorative Study of the Local Council Chair in Flanders - Reuse, Raf; Verhelst, Tom (Politics of the Low Countries, 2025)
Since 2007, Flemish local councils have been entitled to appoint their own chair, ending the mandatory combination of mayoralty and council chairmanship. The Flemish government initiated this reform to encourage the appointment of non-executive councillors as chairs, aiming to strengthen the council’s overall position. Through an explorative study of five types of council chairs, our article examines whether and how chairs can empower the council and whether chairs without an executive office succeed better in doing so. Based on a new typology of the office, we consider the chair’s role along three dimensions: (1) inside empowerment of the council, (2) partisanship and (3) outside empowerment of the office to the community. We find that while all types of chairs strive to empower the council within government, the non-executive chairs act less partisan and emerge as the council’s spokesperson. These findings suggest that a non-executive chair offers more guarantees to advance the council’s position.